2016
DOI: 10.1038/mtm.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-specific targeting by novel capsid-modified AAV6 vectors

Abstract: Recombinant adeno-associated viruses (rAAV) have been widely used in gene therapy applications for central nervous system diseases. Though rAAV can efficiently target neurons and astrocytes in mouse brains, microglia, the immune cells of the brain, are refractile to rAAV. To identify AAV capsids with microglia-specific transduction properties, we initially screened the most commonly used serotypes, AAV1–9 and rh10, on primary mouse microglia cultures. While these capsids were not permissive, we then tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 43 publications
3
88
1
Order By: Relevance
“…In contrast, WT AAV capsids typically do not facilitate microglial transduction, but a recent report described limited infection of microglia using a modified AAV6 capsid 31 . It was unclear whether the new mutant capsid rAAVs used here alter the tropism for astrocytes, oligodendrocytes, and/or microglia.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast, WT AAV capsids typically do not facilitate microglial transduction, but a recent report described limited infection of microglia using a modified AAV6 capsid 31 . It was unclear whether the new mutant capsid rAAVs used here alter the tropism for astrocytes, oligodendrocytes, and/or microglia.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have shown that amongst various AAV serotypes 2, 5, 6, 8 and 9 examined, AAV6 and AAV8 have significantly higher transduction efficiency in microglial cells [56]. Further microglial specificity can be achieved using either novel tropism modified and engineered AAV capsids, robust microglia specific promoter such as TMEM119 [57] and/or by employing neuronal detargeting by incorporating mir-124 target sequences in the AAV 3’UTR [58,59]. Although AAV has been successfully used to achieve genome editing in in vitro primary neuronal cultures as well as postmitotic neurons in vivo [60,61], one of the potential concerns regarding the use of AAV to achieve gene editing in vivo is the cellular immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetically engineered mice, advances in viral-mediated transgene delivery in vivo to individual CNS cell types [199] would further tease apart the impact of APOE expression on brain homeostasis and disease progression in a cell-autonomous manner. For example, use of two recently engineered AAV serotypes that are able to differentially transduce astrocyte (AAV-PHP.A) [199] or microglial (rAAV6 with F4/80 or CD68 promoter) [200] populations may allow for rapid in vivo assessment of cellular APOE effects especially regarding the protective effect of the APOE ε2 allele, and more importantly, the therapeutic potential of expressing APOE ε2 in a specific CNS cell type independent of inherent APOE genotype. Additionally, inducible expression of APOE provided by technologies such as these may define the therapeutic time window during brain aging and disease course.…”
Section: Summary and Perspectivementioning
confidence: 99%